Precursor and preparation method thereof, positive electrode material and preparation method thereof, battery

The precursor of the core-shell structure is prepared by co-precipitation method and sintered in lithiation. A stable cladding layer is formed in combination with the oxidation process, which solves the problem of poor capacity retention and circulation performance of lithium-rich manganese-based materials, and significantly improves the battery Cyclic performance and structural stability.

CN118833865BActive Publication Date: 2024-12-24GANZHOU NOVA TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411269857.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-24
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The low ion diffusion coefficient and irreversible structural phase change of lithium-rich manganese-based materials lead to poor capacity retention and cycling performance, affecting the electrochemical performance of the battery.

Method used

采用共沉淀法制备核壳结构的前驱体,并通过锂化烧结制备改性富锂锰基正极材料,包覆层中包括LiFe5O8材料和Li1+xMn1-xO2,通过氧化工序完全氧化亚铁离子,形成稳定的包覆层以提高结构稳定性。

Benefits of technology

The cycling performance and capacity retention rate of the positive electrode material are significantly improved, element escape is suppressed, and the chemical stability and electrochemical performance of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118833865B_ABST
    Figure CN118833865B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery materials, and discloses a precursor and a preparation method thereof, a positive electrode material and a preparation method thereof, and a battery. The precursor is prepared by a coprecipitation method, and then the precursor is lithiated and sintered to obtain the positive electrode material. The coating layer of the positive electrode material includes LiFe5O8 material and Li 1+x Mn 1‑x O2 material, Li in the coating layer 1+x Mn 1‑x The O2 material plays a transitional role, reducing the capacity reduction of the positive electrode material due to coating; the Fe-O in the LiFe5O8 material in the coating layer has good structural stability, which can inhibit the element escape of the lithium-rich positive electrode material under high voltage, improve the structural stability and chemical stability of the positive electrode material, and thus improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery materials and relates to a positive electrode material of a lithium ion battery and a precursor thereof. Background Art

[0002] Lithium-rich manganese-based materials have many advantages such as high energy density, abundant raw materials and low cost. Their theoretical energy density can reach 900Wh / kg, which is much higher than the energy density of the currently widely used lithium iron phosphate materials and lithium nickel cobalt manganese oxide materials. This means that batteries using lithium-rich manganese-based materials can store more electrical energy than batteries using lithium iron phosphate materials or lithium nickel cobalt manganese oxide materials under the premise of the same battery weight, thereby improving the endurance of electric vehicles.

[0003] As the research on lithium-rich manganese-based materials becomes more and more in-depth, technicians have found that the ion diffusion coefficient of lithium-rich materials is low, resulting in poor capacity retention; and the irreversible phase transition process of the layered structure of lithium-rich materials to the spinel structure and structural changes lead to poor cycle performance of lithium-rich materials. During the electrochemical reaction, after the lithium in the lithium-rich material is reversibly released, the oxygen in the structure partially escapes, making the layered structure irreversible, affecting the electrochemical performance of the battery. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a precursor; in the second aspect, the present invention provides a method for preparing a precursor; in the third aspect, the present invention provides a positive electrode material; in the fourth aspect, the present invention provides a method for preparing a positive electrode material; in the fifth aspect, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a precursor, comprising a core and a coating layer coated on at least a portion of the surface of the core, wherein the core has a general formula of Mn(OH) 2 ; The general formula of the coating layer is Mn 1-y Fe y (OH) 2 , 0.28≤y≤0.75.

[0006] In a second aspect, the present invention provides a method for preparing a precursor, comprising the following steps:

[0007] Step 1, continuously introducing a manganese salt solution, a precipitant and a complexing agent into a reaction container under an inert atmosphere and reacting for a certain time;

[0008] Step 2: continuously introduce a manganese salt solution, a ferrous salt solution, a precipitant and a complexing agent into a reaction container under an inert atmosphere and react for a certain period of time to obtain the precursor.

[0009] Preferably, the manganese salt is one or both of manganese nitrate and manganese sulfate; the concentration of the manganese salt solution is 1-3 mol / L.

[0010] Preferably, the ferrous salt is one or both of ferrous nitrate and ferrous sulfate; the concentration of the ferrous salt solution is 1-3 mol / L.

[0011] Preferably, in step 2, the molar ratio of manganese to ferrous iron in the reaction system is 1:0.4-3.

[0012] Preferably, the precipitant is sodium hydroxide; the concentration of the precipitant is 4-6 mol / L.

[0013] Preferably, the complexing agent is aqueous ammonia; the concentration of the complexing agent is 15-25wt%.

[0014] Preferably, the reaction time of step 1 is 10-30 hours; the reaction time of step 2 is 0.4-1 hour; and the pH value of the reaction system in step 1 and step 2 is both 10-11.

[0015] In a third aspect, the present invention provides a positive electrode material, comprising a core and a coating layer coated on at least a portion of the surface of the core, wherein the core has a general formula of Li 1+x Mn 1-x O 2 ; The coating layer includes Li 1+x Mn 1-x O 2 Materials and LiFe 5 O 8 Materials, where 0.1≤x≤0.5.

[0016] In a fourth aspect, the present invention provides a method for preparing a positive electrode material, wherein the positive electrode material is obtained by mixing the above precursor or the precursor prepared by the above preparation method and a lithium source and then sintering the mixture at a high temperature in an oxygen-containing atmosphere.

[0017] Preferably, the process further includes an oxidation step of the precursor before mixing: placing the precursor in hydrogen peroxide for reaction; more preferably, after the oxidation reaction is completed, the precursor is washed with water, washed with alcohol, and dried.

[0018] Preferably, in the oxidation process, the mass ratio of the precursor to hydrogen peroxide is 1:0.01-0.19.

[0019] Further preferably, the mass fraction of hydrogen peroxide is 20-40%; and the oxidation time is 0.5-4h.

[0020] Preferably, the lithium source is any one or more of lithium hydroxide, lithium oxide, lithium carbonate and lithium nitrate.

[0021] Preferably, the molar ratio of lithium in the precursor and the lithium source is 1:1.23-3.

[0022] Preferably, the sintering temperature is 900-1100° C. and the sintering time is 10-30 hours.

[0023] In a fifth aspect, the present invention provides a battery, comprising the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned method for preparing the positive electrode material.

[0024] Compared with the prior art, the present invention has the following obvious beneficial effects:

[0025] (1) The present invention prepares a core-shell structure precursor by coprecipitation, and the precursor is sintered by lithium to prepare a modified lithium-rich manganese-based positive electrode material. The prepared positive electrode material coating layer includes LiFe 5 O 8 Materials and Li 1+x Mn 1-x O 2 Materials, Li in coating 1+x Mn 1-x O 2 It plays a transitional role and reduces the decrease in the capacity retention rate of the positive electrode material due to coating; the LiFe 5 O 8 The Fe-O in the material has good structural stability, which can inhibit the element escape of lithium-rich positive electrode materials under high voltage, improve the structural stability and chemical stability of the positive electrode materials, and thus improve the cycle performance of the battery.

[0026] (2) The preparation process provided by the present invention is simple and easy to operate, which is conducive to promotion and industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 HRTEM image of the precursor prepared in step 1 of Example 1;

[0028] Figure 2 HRTEM image of the modified lithium-rich manganese-based positive electrode material obtained in step 3 of Example 1;

[0029] Figure 3 HRTEM image of the modified lithium-rich manganese-based positive electrode material obtained in step 3 of Example 4;

[0030] Figure 4 The figure is a comparison chart of the cycle performance of Examples 1 to 4 and Comparative Examples 1 to 2. DETAILED DESCRIPTION

[0031] The present invention provides the following specific technical solutions.

[0032] In a first aspect, the present invention provides a precursor, comprising a core and a coating layer coated on at least a portion of the surface of the core, wherein the core has a general formula of Mn(OH) 2; The general formula of the coating layer is Mn 1-y Fe y (OH) 2 , 0.28≤y≤0.75.

[0033] In a second aspect, the present invention provides a method for preparing a precursor, comprising the following steps:

[0034] Step 1, continuously introducing a manganese salt solution, a precipitant and a complexing agent into a reaction container under an inert atmosphere and reacting for a certain time;

[0035] Step 2: continuously introduce a manganese salt solution, a ferrous salt solution, a precipitant and a complexing agent into a reaction container under an inert atmosphere and react for a certain period of time to obtain the precursor.

[0036] The preferred scheme of raw materials is: the manganese salt solution is any one or both of manganese nitrate and manganese sulfate; the concentration of the manganese salt solution is 1-3 mol / L; the ferrous salt solution is any one or both of ferrous nitrate and ferrous sulfate; the concentration of the ferrous salt solution is 1-3 mol / L; the precipitant is sodium hydroxide solution; the concentration of the precipitant is 4-6 mol / L; the complexing agent is ammonia water; the concentration of the complexing agent is 15-25wt%; in step 2, the molar ratio of manganese to ferrous iron in the reaction system is 1:0.4-3; the gas providing the inert atmosphere is a commonly used inert gas for preparing precursors by co-precipitation, preferably nitrogen.

[0037] The preferred scheme of reaction conditions is: the reaction time of step 1 is 10-30 hours; the reaction time of step 2 is 0.4-1 hour; the pH value of the reaction system in step 1 and step 2 is both 10-11.

[0038] In a third aspect, the present invention provides a positive electrode material, comprising a core and a coating layer coated on at least a portion of the surface of the core, wherein the core has a general formula of Li 1+x Mn 1-x O 2 ; The coating layer includes Li 1+x Mn 1-x O 2 Materials and LiFe 5 O 8 Materials, where 0.1≤x≤0.5.

[0039] Li in the coating 1+x Mn 1-x O 2 It plays a transitional role and reduces the capacity reduction of the positive electrode material caused by coating; the LiFe 5 O 8The Fe-O in the material has good structural stability, which can inhibit the element escape of lithium-rich positive electrode materials under high voltage and improve the structural stability and chemical stability of the positive electrode material.

[0040] In a fourth aspect, the present invention provides a method for preparing a positive electrode material, wherein the positive electrode material is obtained by mixing the above precursor or the precursor prepared by the above preparation method and a lithium source and then sintering the mixture at a high temperature in an oxygen-containing atmosphere.

[0041] The preferred preparation process of the positive electrode material includes an oxidation step of the precursor: placing the precursor in hydrogen peroxide for reaction; more preferably, after the oxidation reaction is completed, the precursor is washed with water, washed with alcohol, and dried.

[0042] In the actual production process, an oxidant is used to completely oxidize the ferrous ions in the coating layer of the precursor into ferric ions, so that the iron elements in the coating layer of the positive electrode material obtained after lithium sintering are all +3 valence (i.e., Fe(OH) 3 All converted to LiFe 5 O 8 ). The oxidation process reduces the possibility of other lithium ferrite phases appearing in the coating layer after lithiation sintering, further improving the electrochemical performance of the battery.

[0043] More preferably, in the oxidation process, the mass ratio of the precursor to hydrogen peroxide is 1:0.01-0.19; more preferably, the mass fraction of hydrogen peroxide is 20-40%; and the oxidation time is 0.5-4h.

[0044] In the actual production process, by controlling the above parameters, the degree of oxidation of the precursor is controlled, the possibility of other lithium ferrite phases appearing in the coating layer after lithiation sintering is further reduced, and the electrochemical performance of the battery is further improved.

[0045] Preferably, the lithium source is any one or more of lithium hydroxide, lithium oxide, lithium carbonate and lithium nitrate; and the molar ratio of lithium in the precursor and the lithium source is 1:1.23-3.

[0046] In the actual production process, if the lithium source is too little, it is easy to cause insufficient lithiation of the precursor, which directly affects the main structure and output of the lithium-rich manganese-based positive electrode material, and the electrochemical capacity of the lithium-rich manganese-based positive electrode material will also be greatly reduced due to insufficient lithium. If the lithium source is excessive, after lithium sintering, part of the lithium source does not fully participate in the reaction, resulting in a layer of lithium-containing compounds, such as Li 2 CO 3 , Li 2 O, etc., because lithium-containing compounds are electrochemically inert and cannot participate in the reversible reaction of lithium ions, their attachment to the surface of the material will affect both the ion and electron transport of the material itself and the final electrochemical capacity.

[0047] Preferably, the sintering temperature is 900-1100° C. and the sintering time is 10-30 hours.

[0048] In the actual production process, if the lithiation sintering temperature is too high, the primary particles will aggregate in large quantities, and the generated lithium-rich manganese-based material particles will be larger, thus affecting the electrochemical capacity of the material. If the lithiation sintering temperature is too low, the lithiation is insufficient, so that the precursor cannot be completely lithiated, the lithium source reaction is incomplete, affecting the formation of the final lithium-rich positive electrode material, and reducing the electrochemical capacity of the lithium-rich positive electrode material.

[0049] Finally, the present invention provides a battery, comprising the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned method for preparing the positive electrode material.

[0050] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0051] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0052] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0053] Embodiment 1:

[0054] A method for preparing a positive electrode material comprises the following steps:

[0055] Step 1, nitrogen is introduced to replace the gas in the continuous stirred tank reactor. In the first stage, 2 mol / L manganese sulfate solution, 5 mol / L NaOH solution and 20 wt% ammonia water are continuously introduced into the continuous stirred tank reactor, the flow rate of manganese sulfate solution is 2 L / h, the flow rate of NaOH solution is 4 L / h, the flow rate of ammonia water is 1 L / h, the pH value of the reaction system is maintained at 10-11, and the reaction is carried out for 20 hours; in the second stage, manganese sulfate solution, NaOH solution and ammonia water are continuously introduced, and 2 mol / L ferrous sulfate solution is introduced into the reaction system at a flow rate of 2 L / h, and the reaction is carried out for 1 hour; then, after water washing, alcohol washing and drying, the core of Mn(OH) is obtained. 2 , the coating layer is Mn 0.5 Fe 0.5 (OH) 2 Precursor.

[0056] Step 2, take 8.9g of the precursor and disperse it in 100ml of deionized water solution, then add 0.8ml of 30% hydrogen peroxide to the solution, react for 2h, and obtain the intermediate product after washing with water, washing with alcohol and drying.

[0057] Step 3, mechanically mixing the intermediate product prepared in step 2 with 0.2 mol of lithium hydroxide, placing it in a muffle furnace for high-temperature sintering at 980° C. for 24 hours, and finally obtaining a modified lithium-rich manganese-based positive electrode material.

[0058] Figure 1 This is the HRTEM image of the precursor obtained in step 1 of Example 1. Figure 1 The lattice spacing in the material can be determined to be the internal core of Mn(OH) 2 , there is a 1nm thick Mn layer on the surface 0.5 Fe 0.5 (OH) 2 phase of matter.

[0059] Figure 2 HRTEM image of the modified lithium-rich manganese-based positive electrode material obtained in step 3 of Example 1. Figure 2 It can be seen that the main structure of the material is a layered lithium-rich manganese-based material, and the surface of the material is coated with a layer of spinel structure phase. Under the premise of determining that the precursor contains four elements of Li, Fe, O, and Mn, by comparing the lattice spacing, it can be determined that the coating layer of the positive electrode material includes LiFe 5 O 8 Materials and Li 1+x Mn 1-x O 2 Material.

[0060] Comparative Example 1:

[0061] A method for preparing a positive electrode material comprises the following steps:

[0062] Step 1, introducing nitrogen to replace the gas in the continuous stirred tank reactor, continuously introducing 2 mol / L manganese sulfate solution, 5 mol / L NaOH solution and 20 wt% ammonia water into the continuous stirred tank reactor, the flow rate of manganese sulfate solution is 2 L / h, the flow rate of NaOH solution is 4 L / h, the flow rate of ammonia water is 1 L / h, the pH value of the reaction system is maintained at 10-11, and the reaction is carried out for 21 hours; then washing with water, washing with alcohol, and drying to obtain Mn(OH) 2 Precursor.

[0063] Step 2, take 8.9g of the precursor and disperse it in 100ml of deionized water solution, then add 0.8ml of 30% hydrogen peroxide to the solution, react for 2h, and obtain the intermediate product after washing with water, washing with alcohol and drying.

[0064] Step 3, taking 8.9 g of the intermediate product prepared in step 2 and mixing it mechanically with 4.8 g of lithium hydroxide, placing it in a muffle furnace for high-temperature sintering at 980° C. for 24 hours, and finally obtaining a lithium-rich manganese-based positive electrode material.

[0065] Comparative Example 2:

[0066] A method for preparing a positive electrode material comprises the following steps:

[0067] Step 1, nitrogen is introduced to replace the gas in the continuous stirred tank reactor. In the first stage, 2 mol / L manganese sulfate solution, 5 mol / L NaOH solution and 20 wt% ammonia water are continuously introduced into the continuous stirred tank reactor, the flow rate of manganese sulfate solution is 2 L / h, the flow rate of NaOH solution is 4 L / h, the flow rate of ammonia water is 1 L / h, the pH value of the reaction system is maintained at 10-11, and the reaction is carried out for 21 hours; then, it is washed with water, washed with alcohol, and dried to obtain Mn(OH) 2 Precursor.

[0068] Step 2, taking 8.9 g of the precursor prepared in step 1 and mechanically mixing it with 0.2 mol of lithium hydroxide, placing it in a muffle furnace for high-temperature sintering at 980° C. for 24 hours to obtain a lithium-rich manganese-based positive electrode material.

[0069] Step 3, mix 1.16g of LiFe 5 O 8 After ball milling with 5g of lithium-rich manganese-based positive electrode material, LiFe 5 O 8 Coated lithium-rich manganese-based positive electrode material.

[0070] Embodiment 2:

[0071] A method for preparing a positive electrode material comprises the following steps:

[0072] Step 1, nitrogen is introduced to replace the gas in the continuous stirred tank reactor. In the first stage, 3 mol / L manganese sulfate solution, 5 mol / L NaOH solution and 15 wt% ammonia water are continuously introduced into the continuous stirred tank reactor, the flow rate of manganese sulfate solution is 2 L / h, the flow rate of NaOH solution is 4 L / h, the flow rate of ammonia water is 1 L / h, the pH value of the reaction system is maintained at 10-11, and the reaction is carried out for 10 hours; in the second stage, manganese sulfate solution, NaOH solution and ammonia water are continuously introduced, and 3 mol / L ferrous sulfate solution is introduced into the reaction system at a flow rate of 0.8 L / h, and the reaction is carried out for 0.4 hours; then after water washing, alcohol washing and drying, the core of Mn(OH) is obtained. 2 , the coating layer is Mn 0.7 Fe 0.3 (OH) 2 Precursor.

[0073] Step 2, take 8.9g (0.1mol) of the precursor and disperse it in 100ml of deionized water solution, then add 0.08ml of 30% hydrogen peroxide to the solution, react for 0.5h, and obtain the intermediate product after washing with water, washing with alcohol and drying.

[0074] Step 3: The intermediate product prepared in step 2 is mechanically mixed with 0.0615 mol of lithium carbonate, and then placed in a muffle furnace for high-temperature sintering at 900° C. for 30 hours to finally obtain a modified lithium-rich manganese-based positive electrode material.

[0075] Embodiment 3:

[0076] A method for preparing a positive electrode material comprises the following steps:

[0077] Step 1, nitrogen is introduced to replace the gas in the continuous stirred tank reactor. In the first stage, 1 mol / L manganese sulfate solution, 6 mol / L NaOH solution and 25 wt% ammonia water are continuously introduced into the continuous stirred tank reactor, the flow rate of the manganese sulfate solution is 2 L / h, the flow rate of the NaOH solution is 4 L / h, and the flow rate of the ammonia water is 1 L / h, the pH value of the reaction system is maintained at 10-11, and the reaction is carried out for 30 hours; in the second stage, manganese sulfate solution, NaOH solution and ammonia water are continuously introduced, and then 3 mol / L ferrous sulfate solution is introduced into the reaction system at a flow rate of 2 L / h, and the reaction is carried out for 1 hour; then after water washing, alcohol washing and drying, the core of Mn(OH) is obtained. 2 , the coating layer is Mn 0.25 Fe 0.75 (OH) 2 Precursor.

[0078] Step 2, take 8.9g (0.1mol) of the precursor and disperse it in 100ml of deionized water solution, then add 1.5ml of 30% hydrogen peroxide to the solution, react for 4h, and obtain the intermediate product after washing with water, washing with alcohol and drying.

[0079] Step 3, taking the intermediate product prepared in step 2 and mechanically mixing it with 0.15 mol of lithium oxide, placing it in a muffle furnace for high-temperature sintering at 1100° C. for 10 hours, and finally obtaining a modified lithium-rich manganese-based positive electrode material.

[0080] Embodiment 4:

[0081] A method for preparing a positive electrode material comprises the following steps:

[0082] Step 1, nitrogen is introduced to replace the gas in the continuous stirred tank reactor. In the first stage, 2 mol / L manganese sulfate solution, 5 mol / L NaOH solution and 20 wt% ammonia water are continuously introduced into the continuous stirred tank reactor, the flow rate of manganese sulfate solution is 2 L / h, the flow rate of NaOH solution is 4 L / h, the flow rate of ammonia water is 1 L / h, the pH value of the reaction system is maintained at 10-11, and the reaction is carried out for 20 hours; in the second stage, manganese sulfate solution, NaOH solution and ammonia water are continuously introduced, and 2 mol / L ferrous sulfate solution is introduced into the reaction system at a flow rate of 2 L / h, and the reaction is carried out for 1 hour; then, after water washing, alcohol washing and drying, the core of Mn(OH) is obtained. 2 , the coating layer is Mn 0.5 Fe 0.5 (OH) 2 Precursor.

[0083] Step 2, taking 8.9 g (0.1 mol) of the precursor and mechanically mixing it with 0.2 mol of lithium hydroxide, placing it in a muffle furnace for high-temperature sintering at 980° C. for 24 hours, and finally obtaining a modified lithium-rich manganese-based positive electrode material.

[0084] Figure 3 HRTEM image of the modified lithium-rich manganese-based positive electrode material prepared in Example 4. Figure 3 The lattice spacing in can determine that the surface of the positive electrode material prepared in Example 4 contains not only LiFe 5 O 8 , there is also Li 2 Fe 3 O 4 .

[0085] contrast Figure 1 and Figure 3 It can be reasonably inferred that: in Example 1, the iron element in the precursor coating layer can be completely oxidized to trivalent iron by the hydrogen peroxide oxidation process, and the iron element in the positive electrode material coating layer obtained after lithium sintering is converted into LiFe 5 O 8 In Example 4, there is no hydrogen peroxide oxidation step, so that ferrous ions may exist in the precursor coating layer. The ferrous ions are not completely oxidized during the lithium sintering process, so that the obtained positive electrode material coating layer contains other lithium ferrite phases, such as Li 2 Fe 3 O 4 The physical phases with equal low valence state affect the charge transfer of the positive electrode material in the subsequent reversible lithium insertion and extraction process, and ultimately affect the electrochemical performance of the battery.

[0086] The materials obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were assembled into batteries by the following method:

[0087] The materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were used as positive electrode materials, respectively, and mixed with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The above materials were placed in a small beaker and stirred at a speed of 800 r / min for 2 hours to obtain a slurry. The slurry was coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4 hours, punched into a pole piece with a diameter of 12 mm, and then dried at 105°C in a vacuum drying oven for 4 hours, placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The battery uses a pure metal lithium sheet with a diameter of 16 mm and a thickness of 0.5 mm as the negative electrode, and a porous polyethylene membrane of model Celgard2300 with a diameter of 18 mm as the separator.

[0088] After the battery was assembled, it was aged for 12 h, then activated for 3 cycles at a voltage of 2~4.8 V and a current density of 0.1 C, and then cycled for 100 cycles at a current density of 2 C. Figure 4 This is the cycle performance diagram of the battery.

[0089] Depend on Figure 4 It can be seen that the cycle performance of the battery assembled with the positive electrode material prepared in Example 1 is higher than the cycle performance of the battery assembled with the positive electrode material prepared in Comparative Example 1, indicating that the coating process provided by the present invention can significantly improve the cycle performance and capacity retention rate of the battery.

[0090] The cycle performance of the battery assembled from the positive electrode material prepared in Example 1 is higher than that of the battery assembled from the positive electrode material prepared in Comparative Example 2, indicating that the modified lithium-rich manganese-based positive electrode material provided by the present invention is superior to the direct conversion of LiFe 5 O 8 When coated on the surface of the positive electrode material, the cycle performance is better and the capacity retention rate is effectively improved.

[0091] Comparing the cycle performance curves of the battery assembled from the positive electrode materials prepared in Example 1 and Example 4, the precursor is first oxidized before the lithium mixed sintering, which can oxidize the ferrous ions into ferric ions, and avoid the appearance of other low-valent lithium ferrite phases in the positive electrode material coating layer. Compared with the positive electrode material without a low-valent lithium ferrite phase in the coating layer, the positive electrode material containing a low-valent lithium ferrite phase in the coating layer has a lower degree of improvement in the cycle performance of the battery.

[0092] Comparing the cycle performance curves of the battery assembled from the positive electrode materials prepared in Example 4 and Comparative Example 2, it can be further explained that if the coating material is not doped with low-valent lithium ferrite phase, the electrochemical performance of the battery can be further improved.

[0093] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a precursor, characterized in that: The steps include: Step 1, continuously introducing a manganese salt solution, a precipitant and a complexing agent into a reaction container under an inert atmosphere and reacting for a certain time; Step 2, continuously introducing a manganese salt solution, a ferrous salt solution, a precipitant and a complexing agent into a reaction container under an inert atmosphere, and reacting for a certain period of time to obtain the precursor; The precursor comprises a core and a coating layer coated on at least part of the surface of the core, wherein the general formula of the core is Mn(OH)2; the general formula of the coating layer material is Mn 1-y Fe y (OH)2, 0.28≤y≤0.

75.

2. The method for preparing a precursor according to claim 1, characterized in that: The manganese salt is one or both of manganese nitrate and manganese sulfate; the concentration of the manganese salt solution is 1-3 mol / L; the ferrous salt is one or both of ferrous nitrate and ferrous sulfate; the concentration of the ferrous salt solution is 1-3 mol / L; the precipitant is sodium hydroxide solution; the concentration of the precipitant is 4-6 mol / L; the complexing agent is ammonia water; the concentration of the complexing agent is 15-25wt%.

3. The method for preparing a precursor according to claim 1 or 2, characterized in that: In step 2, the molar ratio of manganese to ferrous iron in the reaction system is 1:0.4-3.

4. The method for preparing a precursor according to claim 1, characterized in that: The reaction time of step 1 is 10-30 hours; the reaction time of step 2 is 0.4-1 hour; the pH value of the reaction system in step 1 and step 2 is both 10-11.

5. A precursor, characterized in that The precursor is prepared by the preparation method according to any one of claims 1 to 4, wherein the precursor comprises a core and a coating layer coated on at least part of the surface of the core, the general formula of the core is Mn(OH)2; the general formula of the coating layer material is Mn 1-y Fe y (OH)2, 0.28≤y≤0.

75.

6. A method for preparing a positive electrode material, characterized in that: The positive electrode material is obtained by mixing the precursor prepared by any one of the preparation methods of claims 1 to 4 or the precursor of claim 5 with a lithium source and sintering them at high temperature in an oxygen-containing atmosphere.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: Before mixing, an oxidation step of the precursor is also included: the precursor is placed in hydrogen peroxide for reaction.

8. The method for preparing the positive electrode material according to claim 7, characterized in that: The mass ratio of the precursor to hydrogen peroxide is 1:0.01~0.19; the mass fraction of hydrogen peroxide is 20~40%; and the reaction time is 0.5~4h.

9. The method for preparing the positive electrode material according to claim 6, characterized in that: The lithium source is any one or more of lithium hydroxide, lithium oxide, lithium carbonate and lithium nitrate; the molar ratio of lithium in the precursor and the lithium source is 1:1.23-3; the sintering temperature is 900-1100°C; and the sintering time is 10-30h.

10. A battery, characterized in that: Including the positive electrode material prepared by any one of the positive electrode material preparation methods of claims 6 to 9.

Citation Information

Patent Citations

  • Li-ion battery positive electrode material with layered-spinel symbiotic structure and preparation method

    CN101447566A

  • Positive active substance, positive electrode employing same and lithium ion secondary battery

    CN105702949A

  • Surface-coated lithium nickel manganese oxide particles and method for producing same

    CN109817968A

  • Composite positive electrode material and preparation method and application thereof

    CN116002649A

  • Sodium-ion battery positive electrode material and preparation method thereof, positive electrode and sodium-ion battery

    CN116741984A